(untitled) (New York, 1995)
Proceedings of a workshop held in Seville, Spain (date not identified), organized by the Institute for Prospective Technological Studies, a specialized service of the European Commission. The aim of the workshop was to identify practical steps toward the improvement of industrial processes and products with a view to long-term sustainable development. The volume is divided into seven sections: international perspectives, environmental management, technology, case study<-->flue gas desulfurization, towards sustainability, the role of financial institutions, and the role of the regulators. Each section concludes with discussion highlights. Annotation c. by Book News, Inc., Portland, Or.
Keywords: Industrial management,Environmental policy,Air quality management; Environmental aspects